Serum Neopterin in Patients with Malignant Melanoma - Beneš Petr (Pteridines, 2009)
Increased serum or urinary concentrations of neopterin have been described in patients with tumors of different primary locations, but reports on neopterin in patients with melanoma are scanty. We have studied serum neopterin and a melanoma marker, S-100-beta, in 41 patients with melanoma. Serum neopterin and S-100-beta were determined by immunoassay. Neopterin concentrations were significantly increased compared to controls only in patients with active disease, but not in patients without evidence of disease activity. Serum neopterin and S-100-beta in patients with active disease were higher than in patients without evidence of disease activity. In patients a significant correlation existed between neopterin and S-100-beta (rs = 0.33, p <0.05), and, in patients without active disease, there was also a correlation between neopterin and age (rs = 0.51, p <0.01). In conclusion, increased serum neopterin in patients reflects disease activity. A significant correlation was observed between serum neopterin and S-100-beta. Future studies are necessary to demonstrate whether the combined measurement of serum neopterin and S-100-beta could be useful in the detection of recurrence in patients with melanoma.